Radiological Measures of Patellofemoral Alignment in Healthy Small-Breed Dogs: Reference Values and Sex Variability - Garnoeva, Radka Stayova (Acta Scientiae Veterinariae, 2023)
Background: The evaluation of vertical kneecap position within the trochlear groove is essential for understanding the anatomical changes that may lead to canine patellar luxation. Unlike other important diagnostic imaging measurements (e.g. measures of pelvic limb alignment), no data on patellofemoral congruence parameters of canine stifles (congruence angle, linear axial patellar displacement, lateral patellofemoral angle, patellar tilt angle) are reported. The aim of this study was to present metric values of these parameters in healthy dogs from small breeds from both sexes in order to use them for identification of animals with increased risk for MPL. Materials, Methods & Results: The study was performed on 44 stifle joints from 22 healthy dogs of both sexes from 4 small breeds (Pinscher, Pomeranian, Chihuahua and Yorkshire terrier). Inclusion criteria were negative patellar displacement and dancing patella tests after orthopaedic examination, lack of femoral and gluteal muscles asymmetry after palpation, lack of signs of long-term proprioceptive dysfunction, normal patellar and withdrawal reflexes after neurological examination. The translation of the patella in the axial plane was evaluated by means of congruence angle and axial linear patellar displacement. The rotation of the patella in the axial plane was evaluated through measurement of lateral patellofemoral angle and patellar tilt angle. Reference ranges of parameters were analysed in agreement with the guidelines of the American College of Veterinary Pathologists for the determination of reference intervals in veterinary species for sample sizes of 40-120 with non-Gaussian distribution - robust method, 95% confidence interval (CI) with 90 percent CI for upper and lower reference limits. All measured patellofemoral congruence angles were negative. Their reference range was from -8.06 o to -0.58o (median value -3o). The axial patellar displacement was negligible, with values ranging from 0.1 to 0.8 mm. Lateral patellofemoral angles in all dogs were open to the lateral side (positive); the computed reference interval was from 21.61o to 41.80o (median 31.5o). Patellar tilt angles ranged from 2o to 8o (median 5o). A statistically significant difference between sexes was demonstrated for angles describing the rotation of the patella in the axial plane: the lateral patellofemoral angle (P = 0.0248) and the patellar tilt angle (P = 0.0004) were greater in stifles of male dogs. Discussion: This is the first study presenting reference values of parameters describing patellofemoral alignment in healthy dogs from small breeds on tangential radiographs. The values of one of most commonly measured parameters on tangential radiographs (the lateral patellofemoral angle) in stifles of small breed dogs were higher than values in humans, supposedly due to the specific joint anatomy. The patellar tilt angle is considered as more objective and not influenced by limb rotation. For the detection of patellar misalignment, the tilt angle was reported to be almost as specific as the congruence angle but more sensitive and more accurate. It is the most specific and sensitive parameter determining the direction of patellar luxation. In male dogs, the median lateral patellofemoral angle was greater than in females (P = 0.0248). Similar tendency was shown for patellar tilt angle that was also greater in male stifles (P = 0.0004). The reported statistically significant between-sex differences in lateral patellofemoral angle and patellar tilt angle with higher values of both angles in stifles of male dogs could be attributed to the better developed femoral muscles, in particular m. vastus medialis and m. sartorius, and to differences in trochlear groove and kneecap morphology. The presented reference intervals may be useful for early detection of subjects with increased risk to medial patellar luxation. Keywords: patellofemoral congruence, small-breed dogs, reference values, sex dimorphism.